Evaluasi Efek Pre-treatment Ultrasonik pada Proses Hidrolisis Enzimatis Ampas Tahu - Farlina Hapsari; Imam Prasetyo,; Wiratni Budhijanto (Departemen Teknik Kimia Fakultas Teknik Universitas Gadjah Mada, 2015)
Utilization of biomass as alternative energy source is one of the attempts to reduce the dependence on petroleum based energy which is currently still used as the primary energy source. Tofu solid waste is one of the potential biomass sources that have not been fully utilized. Tofu solid waste was mostly comprised of complex molecular structures composed of cellulose, hemicellulose and lignin. Various techniques of pretreatments have been studied to change the physical structure and chemical properties of the biomass to improve its digestibility in enzymatic hydrolysis process. This research studied the effect of ultrasonic pretreatment on tofu solid waste prior to the enzymatic hydrolysis to maximize the conversion of the cellulose into glucose. Ultrasonic pretreatment was conducted by using a water bath equipped with ultrasonic equipment (sonicator) run at the wave frequency of 20 kHz and power of 5 kW. Ultrasonic pretreatment with variations of time (10, 20 and 30 minutes) and temperatures (60 °C, 80 °C, 100 °C) were carried out. Following the pretreatment, hydrolysis tests were conducted on pretreated samples using cellulase enzymes in 100 ml batch reactor at 45 oC and pH 5. Samples were taken every 1 hour for 6 hours of the reaction and glucose concentration in every sample was measured. The highest cellulosic conversion in enzymatic hydrolysis was obtained on the biomass which was pretreated with ultrasonic for 20 minutes. Keywords: tofu solid waste, enzymatic hydrolysis, pretreatment, ultrasonic Pemanfaatan biomassa sebagai sumber energi alternatif merupakan salah satu usaha untuk mengurangi ketergantungan terhadap penggunaan energi minyak bumi yang saat ini masih dipandang sebagai sumber energi utama. Ampas tahu adalah salah satu biomassa yang belum termanfaatkan secara maksimal. Ampas tahu merupakan salah satu biomassa yang memiliki struktur molekul yang kompleks, yang terdiri atas selulosa, hemiselulosa dan lignin. Telah banyak publikasi tentang berbagai teknik pretreatment untuk mengubah struktur fisik dan kimia dari biomassa untuk meningkatkan konversi selulosa pada proses hidrolisis enzimatis. Penelitian ini mempelajari pengaruh pretreatment ultrasonik pada ampas tahu sebelum hidrolisis enzimatis. Penelitian ini dilakukan dengan menggunakan waterbath yang dilengkapi alat ultrasonik (sonikator) dengan frekuensi 20 kHz dan power 5 kW. Dalam penelitian ini dipelajari pretreatment ultrasonik dengan variasi waktu (10, 20 dan 30 menit) dan suhu (60°C, 80°C, 100°C). Ampas tahu yang sudah mengalami pretreatment ultrasonik, selanjutnya dihidrolisis dengan menggunakan enzim selulase dalam reaktor batch dengan volume 100 ml pada suhu 45oC dan pH 5. Pengambilan sampel dilakukan setiap 1 jam selama 6 jam reaksi untuk dianalisis kadar glukosa. Konversi tertinggi pada hidrolisis enzimatis diperoleh pada bahan biomassa dengan pretreatment ultrasonik selama 20 menit. Kata kunci: ampas tahu, hidrolisis enzimatis, pretreatment, ultrasonik